I'm a child anorexic - Waldron, Sarah (Australia : BBC Active, 2006)
A look at anorexia in young girls at a specialized London treatment center. This film documents the highs and pitiful lows of their 12-week programme, featuring their own video diaries and conservations with each other
Title from title screen
Executive producer, Samantha Anstiss ; film editor, Graham Taylor ; camera, Jane Winder, Neville Kidd
Narrated by Amanda St. John
DVD Format
Keywords: Anorexia in children; Anorexia nervosa